Faktor Risiko Kejadian Stunting Pada Anak Usia Balita di Wilayah Kerja Puskesmas Mogang Kecamatan Palipi Kabupaten Samosir Tahun 2024 - Duyo, Rosita; Zuska, Fikarwin; Sitorus , Mido Ester J.; Ketaren , Otniel; Manurung , Kesaktian (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Based on the 2023 Indonesian Health Survey (SKI) in Samosir Regency, the prevalence of stunting was 22.4%, with Palipi District recording the highest rate. As of August 2024, the incidence of stunting in Palipi District reached 14.34% (182 toddlers). Although there has been a decline, stunting remains a priority program in Samosir Regency. Objective: This study aims to analyze the risk factors associated with the incidence of stunting among toddlers in the working area of Mogang Public Health Center, Palipi District. Method: This research employed a quantitative design with a cross-sectional approach conducted in the working area of Mogang Public Health Center in 2024. The study sample consisted of 93 mothers with toddlers, selected using accidental sampling techniques. Data were analyzed using univariate, bivariate (Chi-Square test), and multivariate (logistic regression) analyses. Results: The bivariate analysis revealed significant relationships between maternal nutritional status (p=0.000), parenting pattern (p=0.000), maternal education level (p=0.000), family income level (p=0.002), and household sanitation conditions (p=0.000) with the incidence of stunting. However, multivariate analysis identified only three dominant and independent variables: maternal education level (p=0.014; Exp(B)=26.410), parenting pattern (p=0.001), and household sanitation condition (p=0.023). Conclusion: Maternal education level, parenting pattern, and household sanitation are proven to be the dominant factors influencing stunting. Mothers with low education levels are 26 times more likely to have stunted children. Preventive efforts should prioritize interventions targeting these three factors through focused health education programs.